Understanding the process of agricultural technology - Lambrecht, Isabel B.; Vanlauwe, Bernard; Merckx, Roel; Maertens, M. (Elsevier, 2014)
We analyze the adoption of mineral fertilizer in South-Kivu. We model technology adoption as a three-step-process,including awareness, tryout, and adoption; and empirically analyze these steps using cross-sectional farm-household data, and bivariateand Heckman selection probit models. We find that awareness about fertilizer is high (57%) and mainly determined by education andsocial capital. Tryout is low (13% of aware farmers) but positively influenced by extension interventions. Continued adoption is high(70% of tryout farmers) but capital constraints are important and not all extension interventions are effective for continued adoption.Our results entail implications for extension policies in poor areas.